Ekoteologi dan Pengelolaan Limbah Penyulingan Nilam: Studi Kasus pada Petani di Lansot Tomohon - Imanuel Kristen Tuerah Mokorimban; Ramli Sarimbangun (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2026)
Patchouli oil distillation activities in Lansot Village, Tomohon City, have generated serious ecological problems, including water pollution caused by the disposal of distillation waste near residential wells, air pollution from fuel combustion, and machine noise that disturbs public health and comfort. These conditions reflect low ecological awareness and the absence of adequate waste-management regulations and technology. This study aims to develop an ecotheological perspective for patchouli farmers in sustainable waste management based on the concepts of relational ontology and theocentric stewardship by Jorgenson and Padgett. Using a qualitative case-study approach, data were collected through field observation and in-depth interviews with farmers, affected residents, and local government. The findings show that waste problems are not merely technical but rooted in limited ecological education and social tensions reinforced by close kinship ties, which discourage public protest. The study concludes that integrating Christian faith values through ecological discipleship and collaboration between church, government, and farming communities can enable just, participatory, and sustainable waste management.